2021
DOI: 10.1590/1678-4162-11984
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic evaluation of antimicrobial resistance in Staphylococcus spp. isolated from bovine clinical mastitis

Abstract: Bovine clinical mastitis caused by Staphylococcus spp. is a serious and widespread disease in the world of dairy farming. Antimicrobial therapy is of fundamental importance in the prevention and treatment of infectious mastitis, but the indiscriminate use of antimicrobials acts as a determining factor for the spread of the disease. The present study evaluated the resistance profiles of 57 Staphylococcus spp. isolated from bovine clinical mastitis to beta-lactams and gentamicin, relating characteristics of phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…The high percentage of strains resistant to β-lactams in the present study was similar to that observed in other previous studies (Daka et al, 2012;Xavier et al, 2017;Benites et al, 2021). In Brazil, resistance to β-lactams has also been observed from 18 to 95% in S. aureus isolated from bovine milk (Medeiros et al, 2009;Silva et al, 2012;Ferreira et al, 2016;Girardini et al, 2016;Carvalho et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high percentage of strains resistant to β-lactams in the present study was similar to that observed in other previous studies (Daka et al, 2012;Xavier et al, 2017;Benites et al, 2021). In Brazil, resistance to β-lactams has also been observed from 18 to 95% in S. aureus isolated from bovine milk (Medeiros et al, 2009;Silva et al, 2012;Ferreira et al, 2016;Girardini et al, 2016;Carvalho et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…There is a major public and animal health concern about infections caused by antimicrobial resistant S. aureus. Recent studies evaluating S. aureus isolated from bovine mastitis reported resistance of this pathogen to antimicrobials widely used in veterinary and human medicine, especially to β-lactam antibiotics (Oliveira et al, 2012;Xavier et al, 2017;Benites et al, 2021;Freu et al, 2022). Understanding the epidemiology of antimicrobial resistance of S. aureus causing mastitis may allow the development of preventive strategies to decrease existing resistance and prevent the emergence of new strains of resistant S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the ubiquitous nature and acquisition of ARGs by these microbial agents, it is important to understand their epidemiology through the molecular approaches mentioned above ( Srednik et al., 2017 ; Benites et al., 2021 ). The Northwest region of China is an important agricultural and pastoral region with much potential for the dairy industry in Gansu, Ningxia, Qinghai, and Xinjiang provinces, and the status of AMR among NAS, particularly S. haemolyticus isolated from the dairy herd is still unknown in the northwest region of China.…”
Section: Introductionmentioning
confidence: 99%